Pengaruh Modal dan Produktivitas terhadap Pendapatan Nelayan di Kecamatan Tejakula Kabupaten Buleleng - Kadek Linda Ayu Lestari; M. Rudi Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
This study aims to determine the effect of capital and productivity on fishermen's income in Tejakula District, Buleleng Regency. The subjects of this study were fishermen in Tejakula District, Buleleng Regency, while the objects in this study were capital and productivity. The population tested was 1,034 fishermen with a sample of 91 respondents. The sampling technique used was simple random sampling. Data collection was carried out by distributing questionnaires. To analyze the data, this study used SPSS (Statistical Package for the Social Sciences) version 25, with a multiple linear regression analysis method. The results of this study indicate that partially capital and productivity have a positive and significant effect on fishermen's income. While simultaneously capital and productivity together have a positive and significant effect on fishermen's income in Tejakula District, Buleleng Regency. For further researchers, it is advisable to consider other factors such as work experience, labor, selling price, catch and distance traveled.